Conductive Porous Network of Metal–Organic Frameworks Derived Cobalt‐Nitrogen‐doped Carbon with the Assistance of Carbon Nanohorns as Electrocatalysts for Zinc–Air Batteries. Issue 6 (14th February 2018) - Zhang, Jianshuo; Wu, Chuxin; Huang, Meihua; Zhao, Yi; Li, Jiaxin; Guan, Lunhui
Abstract: Herein, we report a new electrocatalyst for the oxygen reduction reaction derived from a bimetallic metal–organic framework and single‐walled carbon nanohorns. Owing to the 3D conductive network offered by the nanohorns, this type of catalyst exhibits comparable performance with the commercial 20 % Pt/C catalyst as well as excellent durability and methanol tolerance at the half‐cell test in an alkaline medium. Moreover, the new electrocatalyst shows higher peak power density (185 mW cm −2 ) than that of Pt/C (160 mW cm −2 ) in addition to a comparable stability in a real Zn–air battery test. A correlation between the value of the peak power densities and pore structures of some parallel samples is studied in detail. Abstract : Taking O2 reduction by the horns : A new electrocatalyst for the oxygen reduction reaction derived from a bimetallic metal–organic framework and single‐walled carbon nanohorns is reported. The 3D conductive network offered by the nanohorns gives the catalyst comparable performance with commercial 20 % Pt/C as well as excellent durability and methanol tolerance in the half‐cell test in alkaline medium. Moreover, the new electrocatalyst shows high peak power density (185 mW cm −2 ).